Social Competences In Times Of An Economic Crises - Łupicka, Anna (Journal of Positive Management, 2023)
Purpose: In a turbulent economic environment, dealing with global changes brought about by pandemics and war conflicts, the use of legacy social competences needed to successfully run companies in supply chains has been challenged. Using legacy tools is not enough, as social competencies need to meet the digitalization of supply chains. The purpose of this article is to outline the patterns of competencies during economic crises and to establish the suitability of specific social competencies for running a business in a turbulent environment. Design/Methodology/Approach: A survey of selected pharmaceutical industry experts was conducted in 2017 and 2020. These experts are highly qualified managers employed by transnational companies. Respondents were asked to determine the importance and relevance of the social competences chosen. Ten experts participated in the study and completed a survey form. The pharmaceutical sector was selected for the survey. This choice was motivated primarily by its specificity. The pharmaceutical sector is of exceptional importance, not only economically, but also socially, providing medicines to save lives. Findings: When analysing social competencies, one can see a variety of intercultural skills, foreign language skills, the ability to compromise, the ability to transfer knowledge and, finally, the ability to adapt to change. This is a must-have set for managers who want to manage international teams in times of economic crises. Implications/limitations: The proposed set of social competences and the pattern of management of these competences is so universal that comparative analysis in many industries can be carried out using it. It is also worth considering comparative studies in several countries of the same industry. Originality/value: This paper aims to answer the following question: which social competences are proving essential for future managers in the pharmaceutical industry in an unstable environment? The answer to this question is crucial for research and educational institutions aiming to develop social competences in future leaders. Keywords: social competence, economic crisis, key competencies, social capital Paper type: Conceptual paper